EFEKTIFITAS MEDIA PEMBELAJARAN PERMAINAN LUDO TERHADAP MAHARAH QIRO’AH DI SMA MUHAMMADIYAH 2 SIDOARJO - Hasanah, Huswatun; Hikmah, Khizanatul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Arabic language learning can be fun and increase students' enthusiasm for learning if the learning is packaged in an exciting way, not seeming boring and difficult, namely with learning media. Learning media in the modern era now has many types and can utilize surrounding items or games that are packaged in an interesting way. Like the Ludo game which can be used as an interactive game media for students which can be proven by the difference in value between the Pretest value and the Posttest value using 35 respondents, the average value obtained before the media was 65.66 with a standard error of 0.646 and 35 respondents who were given the media, the average value was 81.49 with a standard error of 0.664, indicating that the Ludo game learning media can increase the maharah qiroah.